2022
DOI: 10.3390/plants11182416
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobacteria Mitigate the Negative Effect of Aluminum on Pea Growth by Immobilizing the Toxicant and Modulating Root Exudation

Abstract: High soil acidity is one of the main unfavorable soil factors that inhibit the growth and mineral nutrition of plants. This is largely due to the toxicity of aluminum (Al), the mobility of which increases significantly in acidic soils. Symbiotic microorganisms have a wide range of beneficial properties for plants, protecting them against abiotic stress factors. This report describes the mechanisms of positive effects of plant growth-promoting rhizobacteria Pseudomonas fluorescens SPB2137 on four pea (Pisum sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 79 publications
1
17
0
Order By: Relevance
“…The observed wheat growth promotion by Ps. fluorescens SPB2137 was probably due its ability producing auxins and possessing ACC deaminase activity, which was recently demonstrated on pea plants (Belimov et al, 2022). Strains B. subtilis 124-11 and Sphinhomonas sp.…”
Section: Resultsmentioning
confidence: 81%
“…The observed wheat growth promotion by Ps. fluorescens SPB2137 was probably due its ability producing auxins and possessing ACC deaminase activity, which was recently demonstrated on pea plants (Belimov et al, 2022). Strains B. subtilis 124-11 and Sphinhomonas sp.…”
Section: Resultsmentioning
confidence: 81%
“…L30 (MIC and MLC equal to 5 and 30 mg Al L -1 , respectively) improving Al tolerance of barley plants (Belimov, Kunakova, and Gruzdeva, 1998) and Ps. fluorescens SPB2137 (MIC equal to 5 mg Al L -1 ) improving Al tolerance of pea plants (Belimov et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Recently we showed that PGPR Pseudomonas fluorescens strain SPB2137, initially selected as a biocontrol bacterium (Shaposhnikov et al, 2019), improved Al tolerance of pea due to immobilization and exclusion of this toxicant from root zone (Belimov et al, 2022). Although this strain immobilized Al, produced auxins and possessed ACC deaminase activity, it was relatively sensitive to Al, and its effects on plants were sometimes insignificant.…”
Section: Micro-biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Plants growing in acidic soils suffer from elevated concentrations of mobile aluminum ions ( 1 ). An essential feature of the species Cupriavidus basilensis is its ability to resist toxic metals ( 2 4 ) and degrade xenobiotics ( 5 7 ).…”
Section: Announcementmentioning
confidence: 99%